The Effects of Anthocyanins in Purple Sweet Potato Extract to the Level MDA and NO Sputum Asymptomatic Smokers - Ni Luh Putu Eka Arisanti; Helmia Hasan (Jurnal Respirologi Indonesia, 2018)
Backgrounds: Cigarette consist of 4000 chemical substances which can induce oxidative stress. In lungs, oxidative stress can cause lipid peroxidation, which produce MDA that leads to DNA damage, gene mutations, and loss of repair. Cigarette can also reduce the activity of endogenous Nitric Oxide (NO). Decrease of physiologic NO can cause dysfunction of the endothelium, pulmonary vasoconstriction, bronchospasm, mucous hypersecretion, reduction of mucociliary clearance, and airway remodeling. This damage can be prevented by antioxidant. The content of antosianin in purple cassava (purple sweet potato) is a potent antioxidant that can prevent oxidative stress. The aim of this study is to find out the effects of antosianin administration on MDA and NO sputum level in asymptomatic smoker. Methods: This study is an experimental study with randomized controlled trial pre–post test controlled group design, that performed on outpatient clinic of dr. Soetomo hospital. Results: The result of this study shows that MDA level in treatment group were significantly decrease P=0.0001 between pre (336,90 ng/ml) and post treatment (165,30 ng/ml) compare with control group that shows the opposite effect. In the control group, there was an increase of MDA level both before (416,00 ng/ml) and after placebo was given (476,00 ng/ml). The NO level in treatment group increase but it is not statistically significant between pre (40,80 ng/ml) and post treatment (78,30 ng/ml). The increase of NO level also occured in control group but it is not statistically significant between before (66,67 ng/ml) and after placebo was given (72,00 ng/ml), with the increment was higher in treatment group (6,66 ng/ml) compare with control group (0.53 ng/ml). Conclusions: The MDA sputum level were significantly decrease after the administration of antosianin extract from purple sweet potato in asymptomatic smoker. There were no significant increment of sputum NO level after the given of antosianin extract from purple sweet potato in asymptomatic smoker. (J Respir Indo 2018; 38(2): 64-74)